Mineral Nutrients and Malt Quality of Spring Barley (Hordeum vulgare L.) - Munzert, M.; Baumer, M.; Blum, U.; Wurzinger, A.; Henkelmann, G.; Herz, M.; Holland-Moritz, H. (BrewingScience, 2009)
Samples of barley grains from 10 varieties and 8 locations were analysed on 48 mineral nutrients and 13 malt quality parameters. The article presents means, ranges of variation and (expanded) measurement uncertainties. For many elements a significant influence of varieties could be found. The statistical analysis includes the calculation of coefficients of correlation between the element content and the quality parameters using a covariance analysis in order to eliminate the variety effects (partial coefficent rp). The closest positve rp (adjusted by varieties) to malt quality have been found for K, Pb, Mo and Na. Most of minerals correlate negatively to the malt quality index, especially Zn (rp = -0,67), Mg (rp = -0,47) and Fe (rp = -0,43). The opposite behaviour of zinc in malt and yeast is discussed, as well as the physiological background of the minerals with relation to the malt quality and the practical relevance of the results for farming and breeding.